Design and evaluation of sustained release mucoadhesive film of sumatriptan succinate containing grafted co-polymer as the platform - Surajpal Verma; Rajiv Kumar Tonk; Mohammed Albratty; Hassan Ahmad Alhazmi; Asim Najmi; Ravi Kumar; Mohit Kumar; Mohamad Taleuzzaman; Gourav Swami; Md Shamsher Alam (Elsevier, 2022)
Purpose: The primary goal of this research is to improve the bioavailability and efficacy of Sumatriptan succinate by incorporating it in the mucoadhesive film for the treatment of migraine. Mucoadhesive film offers an excellent substitute to deliver the drug in the systemic circulation and eliminate the chance of first-pass metabolism. Method: Using central composite design (CCD), various formulations were created by incorporating polymer, plasticizer, and water, and an optimized preparation was created using statistical screening. The optimization has been performed by applying a 34 factorial method based on dependent variables such as Drug content (%), Swelling index (%), Folding endurance (Number of times), and Mucoadhesive strength (g). Results: The actual experimental values obtained were compared with those predicted by the mathematical models. Formulation S9 was selected as an optimized formulation because it showed the lowest standard deviation between predicted and actual values compared to other formulations. In the case of the S9 formulation, approximately 77.12% of the drug was released within 24 h, but initially, it showed burst release. In addition, the in-vitro release of pure drug suspension showed 99.32% drug release within 2 h. That signified that the developed formulation provides sustained release due to presence of grafted co-polymer. Conclusion: Formulation holding drug-loaded grafted film showed decent sustained and controlled drug release characteristics compared to a pure drug suspension. S9 formulation showed better results than other formulations in drug content, swelling index, folding endurance, and mucoadhesive strength, which is further used to treat migraine.